GROWTH, MORTALITY AND FOOD HABIT OF LIZARDFISH SAURIDA UNDOSQUAMI RICHARDSON (1848) IN KHOR AL-AMYA, NW ARABIN GULF. - Mutlak, F. M. (Iraqi Journal of Aquaculture, 2022)
Some biological aspects of lizardfish Saurida undosquamis in Khor AL-Amya, NW Arabian Gulf were studied through August 1999 to July 2000. The annual catch rate was 0.33 Kg/h with a maximum of o.5 Kg/h in March and the minimum o.2 Kg/h in July and August. Lizardfish was non resreseuted though out the period from December to February. The growth (L½, K, to) obtained forming Von Bertlanffy equation were as follow: Lt= 282 [1-e –0.53 (t+0.26) ]. The mortality coefficient of total Z, natural M and fishing F were estimated to be 1.218, 0.576, and 0.642. Hence the exploitation rate E was 0.52. The food components of 214 stomachs were examined. The empty stomachs constituted 19.16%. Fish subsist at part of preys forming 80.1% by number and 83.2% by occurrence. Small fishes of Upeneus sulphureus and Leiognathus bindus were the most species preged by S. undosquamis. Crustacea was of secondary importance (18.3% number and 24.1% occurrence) as fish food represenred mainly by shrimps and less of lobster and crabs. The third group of food components was mollusca cephalopod, which coustitionl 1.6% by number and 2.8% by occurrence.